Cell-Free In Vitro Protein Synthesis of Polyketide Synthase Proteins for Production of Natural Products - Sarmales-Murga, Christopher Antonio (Université d'Ottawa / University of Ottawa, 2020)
Heterologous expression of multigene biosynthetic pathways is an essential tool in the study of natural product biosynthesis. Due to its in vivo nature, this process is often limited by, for example, toxicity of the encoded natural product or its biosynthetic proteins, or competition of the biosynthetic proteins with other cellular enzymes for key small molecule building blocks. Cell-free in vitro transcription and translation can overcome some of these limitations. Natural product toxicity is rendered moot in cell-free systems since they are not alive and contain only the necessary proteins, rRNAs, cofactors, substrates, and energy sources for transcription and translation of proteins. As exogenous chemicals can be easily added to the system, building blocks supply issues can be readily solved. We thus investigated using cell-free protein synthesis (CFPS) to biochemically reconstitute the biosynthetic pathway for the fungal polyketide natural product monocillin II. Significant optimization enabled cell-free expression of the full-length monocillin II polyketide synthase (PKS) proteins Rdc5 and Rdc1 directly from plasmids containing their genes under control of the T7 promoter. Correct post-translational modification of the apo-acyl carrier protein domain of the PKS proteins was confirmed by SFP-mediated transfer of a fluorescently modified phosphopantetheinyl group from a chemically modified CoA analog. Unfortunately, treatment of the CFPS produced holo-PKS proteins with their native substrates, malonyl-CoA and NADPH, did not lead to the expected production of detectable levels of monocillin II. Our work suggests that while the CFPS system can generate full length PKS proteins that are sufficiently folded to be recognized, and post-translationally modified by SFP, one or more of the required catalytic domains on these large multidomain proteins is in an inactive state, preventing production of the final product. Identifying non-functional domains, and addressing the issue, may make CFPS an appealing strategy for characterizing PKS biosynthetic gene clusters and prototyping engineered PKS systems.
Keywords: Natural Products; Polyketide Synthases; Cell-Free; Protein Biosynthesis; In-Vitro; Radicicol; Monocillin II; Cell-Free In vitro Protein Synthesis